UXT attenuates the CGAS-STING1 signaling by targeting STING1 for autophagic degradation. Issue 2 (1st February 2023) - Pan, Mingyu; Yin, Yue; Hu, Tongyu; Wang, Xinxia; Jia, Tian; Sun, Jing; Wang, Quanyi; Meng, Wei; Zhu, Juanjuan; Dai, Chunsun; Hu, Haiyang; Wang, Chen
ABSTRACT: STING1 (stimulator of interferon response cGAMP interactor 1), the pivotal adaptor protein of CGAS (cyclic GMP-AMP synthase)-STING1 signaling, is critical for type I IFN production of innate immunity. However, excessive or prolonged activation of STING1 is associated with autoinflammatory and autoimmune diseases. Thus, preventing STING1 from over-activation is important to maintain immune homeostasis. Here, we reported that UXT (ubiquitously expressed prefoldin like chaperone), a small chaperone-like protein, was essential to prevent the excessive activation of STING1-mediated type I IFN signaling through autophagic degradation of STING1 via SQSTM1 (sequestosome 1). Upon DNA mimics or cyclic GMP-AMP (cGAMP) stimulation, UXT specifically interacted with STING1 and promoted STING1 degradation through selective macroautophagy/autophagy. Moreover, UXT was required for more efficient autophagic degradation of STING1 by facilitating the interaction of SQSTM1 and STING1. The in vivo role of UXT in attenuating the CGAS-STING1 signaling was further confirmed in the mouse model of DNA-virus infection and the TMPD (2, 6, 10, 14-tetramethylpentadecane)-induced murine lupus model. Intriguingly, the expression of UXT was consistently impaired and exhibited a remarkable inverse correlation with type I IFN signature in the leukocytes and PBMCs (peripheral blood mononuclear cells) of several large SLE (systemic lupus erythematosus) cohorts. Importantly, the replenishment of UXT effectively suppressed the production of IFNs and ISGs in the PBMCs of SLE patients. Taken together, our study reveals a novel regulatory role of UXT in autophagic degradation of STING1 to maintain immune homeostasis. UXT might be a potential therapeutic target for alleviating aberrant type I IFNs in autoimmune diseasesAbbreviations : 3-MA: 3-methyladenine; BMDMs: bone marrow-derived macrophages; cGAMP: cyclic GMP-AMP; CGAS: cyclic gmp-amp synthase; cKO: conditional knockout; CXCL10: C-X-C motif chemokine ligand 10; GAPDH: glyceraldehyde-3-phosphate dehydrogenase; HSV-1: herpes simplex virus type 1; HTDNA: herring testes DNA; IFIT1: interferon induced protein with tetratricopeptide repeats 1; IFNA4: interferon alpha 4; IFNB: interferon beta; IRF3: interferon regulatory factor 3; ISD: interferon stimulatory DNA; ISGs: IFN-stimulated genes; MAP1LC3B/LC3B: microtubule associated protein 1 light chain 3 beta; MEFs: mouse embryonic fibroblasts; RNA-seq: RNA sequencing; PBMCs: peripheral blood mononuclear cells; RSAD2: radical S-adenosyl methionine domain containing 2; SLE: systemic lupus erythematosus; SQSTM1: sequestosome 1; STING1: stimulator of interferon response cGAMP interactor 1; TBK1: TANK binding kinase 1; TMPD: 2, 6, 10, 14-tetramethylpentadecane; UXT: ubiquitously expressed prefoldin like chaperone.